Dynamic Behavior of Nanocomposites Reinforced with Multi-Walled Carbon Nanotubes (MWCNTs) - Her, Shiuh-Chuan (Materials (Basel), 2013)
The influence of multi-walled carbon nanotubes (MWCNT) on the structural dynamic behavior of MWCNT/epoxy nanocomposites was investigated. Two different types of MWCNTs, pristine MWCNT and functionalized MWCNT, were used in this study. Carboxylic acid-functionalized MWCNTs (MWCNT-COOH) were obtained by oxidation pristine MWCNTs via sonication in sulfuric-nitric acid and characterized by Fourier transform infrared spectroscopy (FTIR). Dynamic behaviors of the MWCNT reinforced nanocomposite including the natural frequency and damping ratio were determined using free vibration test. Experimental results showed that the damping ratio of the nanocomposite decreases with the increase of the MWCNT addition, while the natural frequency is increasing with the increase of the MWCNT addition. Functionalized MWCNTs improved the interfacial bonding between the nanotubes and epoxy resin resulting in the reduction of the interfacial energy dissipation ability and enhancement of the stiffness.